Demographic Factors Affecting Sexual Dysfunction in Postmenopausal Women - Seyedeh Zahra Masoumi; Narges Alavipour; Parisa Parsa; Farideh Kazemi (Journal of Education and Community Health)
Aims: Sexual dysfunction is the common problem in menopause, which can be affected by demographic factors. The aim of this study was to investigate the demographic factors affecting sexual dysfunction in postmenopausal women. Instrument & Methods: This cross sectional descriptive-analytic study was performed on 315 postmenopausal women referred to health care centers in Hamadan in 2018 who were selected by purposive sampling method. The research tools were demographic questionnaire and the female sexual function index (FSFI). To investigate the relationship between different factors and sexual function, univariate and multivariate linear regression were used. Findings: The mean age of participants was 54.15±4.24 years old. The mean score of sexual function was 18.92±4.25, which indicates an undesirable sexual function in postmenopausal women. By increasing the frequency of spouse's marriage, the sexual function score decreased by 2.45 scores (p=0.006). Also, the sexual function score in those who did not have a marriage satisfaction was 5.58 scores less than those who were satisfied with their marital status (p<0.001). Conclusion: The sexual function in studied postmenopausal women is undesirable and they have abnormalities in all areas except sexual pain. There are also relationship between the frequency of spouse's marriage and the satisfaction of marriage with sexual function in postmenopausal women.